2009
DOI: 10.1002/micr.20619
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary reconstruction using anterolateral thigh flap and bone grafts

Abstract: The good results obtained using this technique encourage the choice of the association of anterolateral thigh and bone grafts for reconstructing maxillary complex defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…Wong et al 18 described in 2009 a technical note for the ALT musculocutaneous flap harvesting, underlining the importance of musculocutaneous perforators identification and preservation at the beginning of the dissection that has to be performed opening the intermuscular septum and unroofing the musculocutaneous perforators. We recently described the use of the free ALT musculocutaneous flap and bone grafts association for maxillary reconstruction; 19 however, as far as we know, other articles dedicated specifically to free ALT musculocutaneous flap patients series were published only in the last year and only in Chinese literature. Xia et al 20 reported their experience with ALT musculocutaneous flap for tongue and mouth floor reconstruction in 14 cases, while Liu et al 21 reported a series of 109 free ALT musculocutaneous flaps for reconstruction of soft tissue defects following en block resection of tongue cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Wong et al 18 described in 2009 a technical note for the ALT musculocutaneous flap harvesting, underlining the importance of musculocutaneous perforators identification and preservation at the beginning of the dissection that has to be performed opening the intermuscular septum and unroofing the musculocutaneous perforators. We recently described the use of the free ALT musculocutaneous flap and bone grafts association for maxillary reconstruction; 19 however, as far as we know, other articles dedicated specifically to free ALT musculocutaneous flap patients series were published only in the last year and only in Chinese literature. Xia et al 20 reported their experience with ALT musculocutaneous flap for tongue and mouth floor reconstruction in 14 cases, while Liu et al 21 reported a series of 109 free ALT musculocutaneous flaps for reconstruction of soft tissue defects following en block resection of tongue cancer.…”
Section: Discussionmentioning
confidence: 98%
“…T he anterolateral thigh (ALT) flap, first described as a septocutaneous perforator-based flap by Song et al (1) in 1984, has recently gained popularity and has become an important option for reconstruction of multiple anatomical locations such as the head and neck (3)(4)(5)(6)(7)9,10,(12)(13)(14)16,(18)(19)(20)(21)(22)(23)(25)(26)(27)(28)(29)(30)32,34,36,38,39,(41)(42)(43), upper (15)(16)(17)(18)(19)26,32,35,37,38,42) and lower (8,(16)(17)(18)(19)22,24,…”
mentioning
confidence: 99%
“…Other authors have shown the utility of the combination of bone grafts and rectus abdominis or latissimus dorsi free flaps. Bianchi et al [31] described the use of a myocutaneous anterolateral thigh free flap combined with nonvascularized iliac crest or calvarial bone grafts for Brown class 3 defects in a series of eight patients. In all cases, the bone grafts were draped in revascularized muscle and fascia with the skin paddle folded to reline the oral cavity.…”
Section: Soft Tissue With Bone Graft Reconstructionmentioning
confidence: 99%
“…A variety of donor sites providing soft tissue only or soft tissue with bone have been described in the literature, including the radial forearm [14][15][16][17][18], rectus abdominis [19,20], fibula [21][22][23][24], scapular [25][26][27], iliac crest [28,29], and anterolateral thigh [30,31] systems of free flaps. In all cases of midfacial reconstruction, the individual characteristics of the defect and the patient will guide which type of reconstruction is undertaken.…”
Section: Reconstructive Choicesmentioning
confidence: 99%
See 1 more Smart Citation